2018
DOI: 10.1177/1120700018811310
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion rates with intravenous tranexamic acid in total hip arthroplasty performed using the direct anterior approach

Abstract: Introduction: Tranexamic acid (TXA) has been shown to reduce blood loss and transfusion requirements in patients undergoing total hip arthroplasty (THA). Most studies have focused on TXA in THA performed using a posterior approach (PA) or lateral approach. The aim of this study was to analyse the efficacy of TXA in patients undergoing THA using the direct anterior approach (DAA). Patients and methods: Using our institutional database, a retrospective analysis was conducted on consecutive primary THA performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 35 publications
3
10
2
Order By: Relevance
“…We speculate that the reason is that these patients in our study have a younger age, lower of BMI and shorter of operative time than those in Fraval et al [12] study. In addition, our results are not exactly the same as Free et al [13] study, they found that the transfusion rate after TXA was 1.2% in THA using DAA, which was signi cantly lower than the transfusion rate of 11.1% in the control group. We speculate that the reason is that these patients in our study have a younger age, lower of BMI and lower of ASA score than those in Free et al [13] study.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…We speculate that the reason is that these patients in our study have a younger age, lower of BMI and shorter of operative time than those in Fraval et al [12] study. In addition, our results are not exactly the same as Free et al [13] study, they found that the transfusion rate after TXA was 1.2% in THA using DAA, which was signi cantly lower than the transfusion rate of 11.1% in the control group. We speculate that the reason is that these patients in our study have a younger age, lower of BMI and lower of ASA score than those in Free et al [13] study.…”
Section: Discussioncontrasting
confidence: 91%
“…In addition, our results are not exactly the same as Free et al [13] study, they found that the transfusion rate after TXA was 1.2% in THA using DAA, which was signi cantly lower than the transfusion rate of 11.1% in the control group. We speculate that the reason is that these patients in our study have a younger age, lower of BMI and lower of ASA score than those in Free et al [13] study. Whether TXA can reduce the transfusion rate for THA via DAA requires more sample size and more prospective studies to determine.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Tranexamic acid (TXA) reduces bleeding and transfusion in primary total hip arthroplasty (THA) without increasing the risk of venous thromboembolism (VTE) (1)(2)(3)(4)(5)(6). Compared with primary THA, revision THA usually causes more perioperative blood loss and transfusion because of more extensive exposure, longer operation time, and osteotomy.…”
Section: Introductionmentioning
confidence: 99%